Prognostic immune markers identifying patients with severe COVID-19 who respond to tocilizumab - De Biasi, Sara; Mattioli, Marco; Meschiari, Marianna; Lo Tartaro, Domenico; Paolini, Annamaria; Borella, Rebecca; Neroni, Anita; Fidanza, Lucia; Busani, Stefano; Girardis, Massimo; Coppi, Francesca; Mattioli, Anna Vittoria; et al. (Frontiers in Immunology, 2023)
Introduction A growing number of evidences suggest that the combination of hyperinflammation, dysregulated T and B cell response and cytokine storm play a major role in the immunopathogenesis of severe COVID-19. IL-6 is one of the main pro-inflammatory cytokines and its levels are increased during SARS-CoV-2 infection. Several observational and randomized studies demonstrated that tocilizumab, an IL-6R blocker, improves survival in critically ill patients both in infectious disease and intensive care units. However, despite transforming the treatment options for COVID-19, IL-6R inhibition is still ineffective in a fraction of patients. Methods In the present study, we investigated the impact of two doses of tocilizumab in patients with severe COVID-19 who responded or not to the treatment by analyzing a panel of cytokines, chemokines and other soluble factors, along with the composition of peripheral immune cells, paying a particular attention to T and B lymphocytes. Results We observed that, in comparison with non-responders, those who responded to tocilizumab had different levels of several cytokines and different T and B cells proportions before starting therapy. Moreover, in these patients, tocilizumab was further able to modify the landscape of the aforementioned soluble molecules and cellular markers. Conclusions We found that tocilizumab has pleiotropic effects and that clinical response to this drug remain heterogenous. Our data suggest that it is possible to identify patients who will respond to treatment and that the administration of tocilizumab is able to restore the immune balance through the re-establishment of different cell populations affected by SARS-COV-2 infection, highlighting the importance of temporal examination of the pathological features from the diagnosis.